Inflammation and oxidative stress markers in diabetes and hypertension - Pouvreau C; Dayre A; Butkowski EG; de Jong B; Jelinek HF (Dove Medical Press, 2018)
Chloé Pouvreau,1 Antoine Dayre,1 Eugene G Butkowski,2 Beverlie de Jong,2 Herbert F Jelinek2,3 1Faculty of Sciences, University of Poitiers, Poitiers, France; 2School of Community Health, Charles Sturt University, Albury, NSW, Australia; 3Australian School of Advanced Medicine, Macquarie University, Sydney, NSW, Australia Background: Inflammation and oxidative stress are important factors associated with chronic disease such as essential hypertension (HTN) and type 2 diabetes mellitus (T2DM). However, the association of inflammation and oxidative stress in HTN with T2DM as a comorbidity is inconclusive due to the multifactorial nature of these cardiometabolic diseases. Methodology: The influence of pathophysiological factors include genetics, age of patient, and disease progression change throughout the lifespan and require further investigation. The study population included 256 participants attending a rural health screening program who were tested for markers of inflammation, oxidative stress, and coagulation/fibrinolysis. Demographic and clinical variables included, age, gender, systolic and diastolic blood pressures, blood glucose, hemoglobin A1c, estimated glomerular filtration rate, and cholesterol profile. Data were tested for normality, and nonparametric statistics were applied to analyze the sample with significance set at p<0.05. Results: Of the inflammatory markers, interleukin-1β (IL-1β) and IL-10 were significantly different between the control and hypertensive group (p<0.03) and between the HTN+T2DM compared to the HTN group (p<0.05). Significant results for oxidative stress were observed for urinary 8-iso-PGF2α and insulin-like growth factor 1 (IGF-1) between the control and the HTN+T2DM group (p<0.01). Glutathione (GSH) was also significant between the HTN and HTN+T2DM group (p<0.05). Investigation of the progression of HTN also found significant changes in the inflammatory markers IGF-1, monocyte chemoattractant protein 1 (MCP-1), and (MCP-1/IGF-1)*IL-6 (p<0.05). Conclusion: This study demonstrated that 8-iso-PGF2α and erythrocyte GSH may be clinically useful for assessing HTN and HTN with T2DM as a comorbidity, while significant changes in the inflammatory profile were also observed with HTN progression. Keywords: hypertension, type 2 diabetes mellitus, inflammation, oxidative stress, biomarkers